Biological psychology : an introduction to behavioral, cognitive, and clinical neuroscience - Rosenzweig, Mark R. (Sinauer, 2002)
This book explores the biological bases of our experience and behavior: the ways in which bodily states and processes produce and control behavior and cognition, and the ways in which behavior, cognition, and the environment exert their influence on bodily systems. The authors treat biology in a broad sense. As in most textbooks of this sort, there is substantial coverage of the proximate, physiological underpinnings of behavior, but they have also attempted to give due attention to ultimate causes by placing these discussions in an evolutionary framework whenever possible. The focus of the book is human behavior, but the authors include numerous discussions of other species' solutions to the problems of survival as well. Throughout, the text employs a 5-fold approach to biological psychology: descriptive, comparative/evolutionary, developmental, mechanistic, and applied/clinical. The authors emphasize neuroscience research, whether conducted by psychologists or nonpsychologists, that aims to inform our understanding of behavior. Finally, they give special attention to work that explores the remarkable plasticity of the nervous system, with a chapter that emphasizes the particular importance of plasticity in the psychological approach to neuroscience.